Translation Errors Of Noun Phrases: Bahasa Indonesia Into English For Efl Learners - Umar Bakri (Pendidikan Al-Gafari, 2023)
The study aims to identify learners errors in translating the noun phrase Indonesia into English and describe learners' difficulties in translating the noun phrase Indonesia into English. The writer used a qualitative approach. To collect the data, the writer took the data from observation, interview, and documentation. To analyze the data, the writer used Miles and Huberman’s theory are three stages namely reduction, data display, and drawing conclusion. The result of the study consisted of types of learners translating errors in translating noun phrases Indonesia into English. Those demonstrated in the types of learners errors in which Missselection of words. It occurred twenty six times errors. Wrong spelling occurred six times errors. Misordering occurred thirty three times errors. The omission occurred forty eight times errors. Addition occurred seventy five times errors. The last, Misformation occurred twelve times errors. Meanwhile, the learners' difficulties found were such as lack of learners' vocabulary, the necessity of grammar, and lack of learners' understanding of word orders. The first result dominantly occurred in learners' translation error of the noun phrase Indonesia into English was an addition with a total number of errors seventy five. Besides, the second result could be identified as the lack of the learners' vocabulary as the highest difficulty in translating errors of noun phrases Indonesia into English.